(untitled) (Castilla. Estudios de Literatura, 2012)
The comedy of ms. 17.317 from BNE has been attributed to various theater authors of the Spanish Golden Age. It has also been called in different ways throughout its publishing history. In this manuscript is named El negro del Serafín and attributed to Luis Vélez de Guevara. The most famous and repeated transmission is included in Parte Cuarta of Nuevas Escogidas. In this volume is attributed to Mira de Amescua and is titled El negro del mejor amo. This article discusses the censorship of the manuscript to establish relations between the two testimonies.